Strategi Orientasi Pada Industri Manufaktur Kota Surabaya - Ismi Rosyidatul Ummah; Achmad Alfian Azizi; Muhammad Yasin (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to analyze the orientation strategy of the Surabaya city manufacturing industry. The method usedin this research is descriptive qualitative method. Source of data usedderived from secondary data through literature review or what is called a studyliterature collected by the researchers themselves through websites, journals, bulletins, for example taken from the Statistics Agency, company or organizational documents, newspapers and magazines, or other publications. Currently the manufacturing industry in Surabaya continues to experience increased productivity and business expansion after experiencing a decline due to the Covid-19 pandemic. This increase is inseparable from the increasing demand for an increasingly varied market, which has become a driving force for business players to grow and meet market needs. This is what is used in the manufacturing industry, namely market orientation, which includes customer orientation, competitor orientation, coordination between functions, and technology orientation. When a company is market oriented, it shows that the company pays attention to its consumers. Market orientation can be seen from customer orientation and competitor orientation. Customer orientation by researchers is placed as the highest priority in terms of providing superior values to customers.